VAD-doxil versus VAD-doxil plus thalidomide as initial treatment for multiple myeloma: Results of a multicenter randomized trial of the Greek myeloma study group - Zervas, K.; Mihou, D.; Katodritou, E.; Pouli, A.; Mitsouli, C.H.; Anagnostopoulos, A.; Delibasi, S.; Kyrtsonis, M.C.; Anagnostopoulos, N.; Terpos, E.; Zikos, P.; Maniatis, A.; et al. (Annals of Oncology, 2007)
Background: We have previously demonstrated that vincristine, liposomal doxorubicin and dexamethasone (VAD-doxil) is equally effective with VAD-bolus yielding objective response rates of 61% as first-line treatment in multiple myeloma (MM). In a phase II study, the addition of thalidomide to VAD-doxil (TVAD-doxil) proved feasible and increased response rate to 74%. The aim of the present multicenter prospective randomized clinical trial was to compare the efficacy and toxicity of VAD-doxil and TVAD-doxil in previously untreated MM patients. Patients and methods: We enrolled 232 newly diagnosed MM patients aged <75 years, 115 randomized to VAD-doxil (arm A) and 117 to TVAD-doxil (arm B). Patients in arm A received vincristine 2 mg i.v. and liposomal doxorubicin 40 mg/m2 i.v., on day 1 and dexamethasone 40 mg p.o. daily on days 1-4, 9-12 and 17-20 for the first cycle and on days 1-4 for the next three cycles. Patients in arm B received additionally thalidomide 200 mg p.o. daily, at bedtime. Treatment was administered every 28 days. Results: On an intention-to-treat basis, at least partial response was observed, in 62.6% and in 81.2% of patients randomized to arms A and B, respectively (P = 0.003). Progression-free survival (PFS) at 2 years was 44.8% in arm A and 58.9% in arm B (P = 0.013). Overall survival (OS) at 2 years was 64.6% and 77%, in arms A and B, respectively (P = 0.037). Considering overall toxicity, constipation, peripheral neuropathy, dizziness/somnolence, skin rash and edema were significantly higher in arm B compared with arm A (P < 0.01), but grade 3-4 toxicities were low and similar in both arms. Conclusions: The addition of thalidomide to VAD-doxil increases response and PFS rates and probably OS in previously untreated myeloma patients. The superiority of efficacy counterbalances the higher overall toxicity of TVAD-doxil. © 2007 European Society for Medical Oncology.
Keywords: multiple myeloma; Thalidomide; VAD-doxil